Recursos musicais aplicáveis à saúde da criança e do adolescente: contribuições da musicoterapia á clínica pediátrica - Maria Eugenia Castelo Branco Albinati (2008)
INTRODUCTION: This thesis presents an investigation about the therapeutic potential of seven musical resources that are found in activities practiced in Western society: musical games, musical appreciation, singing, musical instruments, creation in music, dance andmusical presentation. METHODOLOGY: The exploratory-descriptive study of the application of these resources to 60 children and adolescents between 1 and 20 years old, through systematic observation and open interviews with their carers and technicians, identified alterations of behaviour perceived in their contact with the music. The mapping ofthe musical resources shows their specificities, possible activities of being developed, and resulting benefits of their therapeutic use, in agreeance with the theories of Music Therapy. The variety of ages and diagnosis of the children and adolescents established the access andbenefits of the musical resources to patients with different capacities of affective, motor and cognitive response. The variety of health spaces (the Music Therapy offices of the Music Therapy Association of Minas Gerais, child medication room of the Borges da Costa Hospital and the Occupational Therapy Isle of the Bias Fortes Hospital) recognized the different forms of the musical practices that are offered in different therapeutic ambiances, without compromising their own dynamics. RESULTS: The musical games make the children/adolescents alert and participating, and give them knowledge and sharing of meaningful moments with others. Musical appreciation gives them access to the expression of different times, spaces and visions of the world, reminding and remaking their own lives, emotions and fantasies. The narrative and mnemonic power of singing help them follow complex sequences and learn information by heart, appeasing them to better their speech andtheir expressive language, and helping them to affirm their individuality beyond their illness. The tonic effect of the musical instruments impulses the child/adolescent to organized movement, elaborated construction and joyful participation in instrumental ensembles. Musical creation opens the way to the construction of a positive identity, the emerging of anunexpected creativity in midst of the psychomotor difficulties, and an adequate and valued way of expressing their feelings and ideas. Dancing enriches their body image and betters their abilities to move. Rehearsals and musical presentations make it possible for them to present themselves in front of the others in a positive form, showing their strength, happiness and capabilities. CONCLUSIONS: Since it is part of human culture, music is familiar to the 12 child/adolescent, to their carers and to health technicians, and stimulates the positive participation of all, focusing on people obscured by the illness. Having children andadolescents with no autonomy as subjects, this investigation was led to realize the enormous participation of the carer and health professional in musical practice, not only to involve the patient, but also for their own appreciation. Their involvement, beyond being a determinantfactor to the success of the treatment of the dependent child/adolescent, benefit this populations forgotten by the health area. Although the coordination of a music therapist would guarantee a better use of the musical resources in relation to the needs of each patient, since music is a common practice to most people and is accessible to non-musicians, the musical activities are easily developed among the patients, their carers and technicians, with positive results for all.